Command authority - Clancy, Tom 1947-2013; Greaney, Mark 1968- (Michael Joseph, 2013)
"The #1 New York Times-bestselling author and master of the technothriller returns with his All-Star team. There's a new strong man in Russia but his rise to power is based on a dark secret hidden decades in the past. The solution to that mystery lies with a most unexpected source, President Jack Ryan"..
Keywords: Suspense fiction; FICTION / Thrillers; FICTION / War & Military; FICTION / Action & Adventure; Ryan, Jack, Sr. (Fictitious character) -- Fiction; Ryan, Jack, Jr. (Fictitious character) -- Fiction; Political fiction; Fiktionale Darstellung